UJI KARAKTERISTIK FISIK DAN KIMIA PAKAN LOKAL DAN IMPOR KUDA PACU MINAHASA - Pongoh, Veity M; Tulung, B.; Tulung, Y L.R. (Universitas Sam Ratulangi, 2015)
PHYSICAL AND CHEMICAL CHARACTERISTICS APPRAISAL OF LOCAL AND IMPORTED RACE HORSES FEED IN MINAHASA The present study was conducted to determine the physical characteristics and nutrient content of racehorse diets both local and imported feed used mostly by race horse breeders in Minahasa region. Race horse breeding management in Indonesia fully adopts methods used in developed countries. Race horse breeders in Minahasa have been practicing of using oats as an imported ingredient to replace local feed rice. This is due to the lack of further testing of local feed, so that race horse breeders practice and rely on using imported feed ingredients to feed their horses just before the horse racing. Â A survey method was used to collect data, using interviews and direct observations on several race horses breeding farms. Types and amount of feed (forage and concentrates) both local and imported given to race horse were taken about 500gr for samples analysis. Data were statistically analyzed using t-test. The results showed that the nutrient content of imported feed ingredients significantly higher (P <0.05) compared with local feed. Physical characteristics (color, flavour, shape, and texture) of local food (rice) was significantly different (P <0.05) from that of imported feed (oats). It can be concluded that the nutrient content of imports feed is higher than that of local feed, and physical characteristics of oat and rice, different in colour, shape, aroma, and texture, on the other hand, oat and rice have the same physical shape. Keywords: Physical characteristics, Chemistry, Race horse, Local Feed, Imported Feed.